2020
DOI: 10.1016/j.cmet.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Boost Mammalian Host NAD Metabolism by Engaging the Deamidated Biosynthesis Pathway

Abstract: Highlights d Bacteria confer host cells with resistance to NAMPT inhibitors (NAMPTis) d Bacteria produce deamidated NAD precursors and prevent NAD depletion d Bacteria rescue NAMPTi-induced toxicity through nicotinamidase PncA d Oral NAM and NR boost in vivo NAD largely via microbiotadependent deamidated pathway

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
165
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(180 citation statements)
references
References 68 publications
15
165
0
Order By: Relevance
“…We performed mass spectrometry (MS) analysis to differentiate between NADH and NADPH changes in the whole cell, using relative quantification to show the more dynamic behavior [ 40 ]. We observed a gradual increase in NAD + (3 fold) and NADH (2.3 fold) levels in HEK293T at 1 h, which then returned to levels comparable to control after 4 and 24 h of NRH exposure ( Fig 6A and 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…We performed mass spectrometry (MS) analysis to differentiate between NADH and NADPH changes in the whole cell, using relative quantification to show the more dynamic behavior [ 40 ]. We observed a gradual increase in NAD + (3 fold) and NADH (2.3 fold) levels in HEK293T at 1 h, which then returned to levels comparable to control after 4 and 24 h of NRH exposure ( Fig 6A and 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…NAMPT modulates processes involved in the pathogenesis of obesity and related disorders by influencing the oxidative stress response [ 12 ], is often overexpressed in tumor tissues, and potentially contributes to the ability of cancer cells to resist oxidative stress [ 19 ]. The levels of NAMPT decrease with aging due to chronic inflammation, oxidative stress, and DNA damage [ 20 ]. In the cardiovascular system, NAMPT exacerbates atherosclerotic inflammation and promotes atherosclerosis development in ApoE mice [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note the NAD + boosting effect of these supplementations might not be as straight forward as initially thought due to the recent discovery that gut microbiota may also play a role in the NAD + boosting effect of dietary NAM. Shats and colleagues recently reported that nicotinamidase (PncA) produced by microbes in the gut actively converts NAM to NA [ 73 ]. NA is then taken up by colonic epithelial cells and further converted to NAD + .…”
Section: Supplementation Of Nad + and Its Precumentioning
confidence: 99%
“…This essentially reroutes the NAM from NAD + salvage pathway to the Preiss–Handler pathway. Furthermore, by tracing the fate of isotope-labeled NAM after treatments, NAD + molecules produced through this mode of NAD + biosynthesis have also been found to represent the major portion of the elevated NAD + pool in murine hepatic cells [ 73 ]. This demonstrated that a host–microbe metabolic interaction can influence the efficacy of certain NAD + boosting nutraceuticals.…”
Section: Supplementation Of Nad + and Its Precumentioning
confidence: 99%